Buddhism and interfaith dialogue part one of a two-volume sequel to Zen and Western thought - Abe, Masao 1915-2006 (Univ. of Hawaiʿi Press, 1995)
"Like all other religions, Buddhism is deeply involved in the religiously pluralistic situation of the world today, and is also involved in inter-religious dialogue. However, the Buddhist view of inter-religious dialogue is significantly different from, say, that of Christianity. In Christianity Jesus Christ, being the only incarnation in history, has an inexplicable uniqueness. It must be maintained even in interfaith dialogue. By contrast, in Buddhism Guatama Buddha is not the only Buddha (an awakened one) but one of many Buddhas. His uniqueness is realised in the fact that he is the first Buddha in human history. Furthermore, the Buddhist teaching of dependent co-origination and emptiness not only provides a dynamic common basis for various religions but also will suggest a creative cooperation amongst world religions. This book clarifies such a Buddhist view of inter-religious dialogue from various perspectives, and it shows a leading Buddhist thinker of the twentieth century engaged in ongoing dialogue with a variety of Western theologies and theologians."--BOOK JACKET.